A study of stormwater runoff from Alexandra township in the juskei river - Campbell, Linda Anne (My University, 1996)
South Africa, like many other developing countries, is faced with rapid urbanisation with the associated increase in the pollution load. Much of this pollution is destined for our watercourses, that eventually run into storage reservoirs which may be used for drinking water or recreational purposes. This pollution is usually attributed to human waste products which include nitrogenous wastes, phosphates, microorganisms, organic material and litter, A 6km stretch of the Jukskei river just downstream of Alexandra Township, was used to determine the different biological, physical and chemical processes that pollutants undergo during natural assimilation, their rates and efficiencies of assimilation in rivers and their impact Oil the environment downstream of the urban area. "Grab" samples were taken over a period which included both low-flow and storm events. Due to the high concentration of nutrients in the run-off from Alexandra Township, the major changes seen were in the biological conversion of organic nitrogen compounds and ammonia to nitrates, in the BOD and in the concentration of dissolved oxygen in the river, with lows of 1.1 to 1.5 mg/l 02 being recorded at Alexandra. A rapid rise in the concentration of faecal coliforms has been seen with a high of 31 million/100 ml being recorded at Alexandra in September, 1994. Sedimentation at the Alexandra site is also a common occurrence with a lot of adsorbed pollutants being effectively removed from the water column with the suspended solids. The QUAL2E water quality model, used by the EPA in the United States, was used to model the reactions that the nutrients, BOD and DO undergo. BOD and DO were modelled very well with r of 0.98 and 0.94 being calculated respectively. QUAL2E did not model tile dissolved potlutants, dissolved phosphorus and ammonia very well with the observed results showing a greater reduction ill these pollutants. A method by which these pollutants adhere to SS and settle out was
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science in Engineering
Keywords: Pollution load; Storm water; Sedimentation; Nitrogenous wastes; Organic nitrogen compounds and ammonia to nitrates